Kinetic studies of amino acid-based surfactant binding to DNA - Santhiya, Deenan; Dias, Rita S.; Dutta, Sounak; Das, Prasanta Kumar; Miguel, Maria G.; Lindman, Bjorn; Maiti, Souvik (Journal of Physical Chemistry B, 2012)
In this work, the binding kinetics of amino acid-based surfactants, presenting different linkers and head groups, with calf thymus (CT)-DNA was studied using stopped-flow fluorescence spectroscopy. The kinetic studies were carried out as a function of Na+ concentration and surfactant-to-DNA charge ratio. The surfactant binding on DNA took place in two consecutive steps, for which the corresponding first and second relative rate constants (k(1) and k(2)) were determined. The fast step was attributed to the surfactant binding to DNA and micelle formation in its vicinity, the slower step to DNA condensation and possible rearrangement of the surfactant aggregates. In general, both relative rate constants increase with surfactant concentration and decrease with the ionic strength of the medium. The architecture of the surfactant was found to have a significant impact on the kinetics of the DNA surfactant complexation. Surfactants with amide linkers showed larger relative rate constants than those with ester linkers. The variation of the relative rate constants with the head groups of the surfactants, alanine and proline, was found to be less obvious, being partially dependent on the surfactant concentration.